U.S. export controls and economic sanctions - Hirschhorn, Eric L.; Egan, Brian James, 1972-; Krauland, Edward J. (New York, NY : Oxford University Press, 2021)
The US government imposes a host of controls on exports of high technology and other items, as well as restrictions on transactions by US persons with disfavored foreign countries, entities, and individuals. Everyone in the US who exports, or does business abroad, must comply with these rules, as fines and jail terms can be imposed on those who do not. This book, written by experts who have decades of experience dealing with these restrictions, addresses in detail the five most important of these regulatory regimes, providing essential information on what and who they cover, what they permit and prohibit, and how to comply with them.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 15, 2021).
Keywords: Export controls -- United States; Embargo